Peningkatan Communication Skills Siswa SMP melalui Media Ethnogames 3D Berbasis Permainan Tradisional Bugis Mabombo-Bombo - Cristina, A. Sindi; Asfar, Andi Muhammad Irfan Taufan; Asfar, Andi Muhamad Iqbal Akbar; Suhardiman, Suhardiman; Idris, Muhammad (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to analyze the improvement of students’ communication skills through the implementation of the Bugis traditional game Mabombo-Bombo integrated with 3D Ethnogames-based learning media. The research employed a quasi-experimental method with a non-equivalent control group design. The subjects were 9th-grade students of SMP Negeri 2 Salomekko, consisting of 30 students in the experimental class and 30 students in the control class selected through purposive sampling. The research instrument was a communication skills test based on three indicators: differentiating ideas, organizing arguments, and attributing reasoning. Data were analyzed using normality test, homogeneity test, and N-gain analysis. The results showed that the experimental class achieved a higher N-gain score (0.7613, high category) compared to the control class (0.3135, medium category). This indicates that integrating the Mabombo-Bombo game into 3D Ethnogames-based learning is more effective in improving students’ communication skills than using Ethnogames 3D alone.